Nghiên cứu ý định sử dụng chatbot và mua sắm trực tuyến của khách hàng: Tiếp cận từ lý thuyết chấp nhận công nghệ và đặc trưng của chatbot - Lê Xuân, Cù (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The purpose of the article is to analyze customers’ use intention toward chatbots and online purchase intention in Vietnam. A research framework of chatbot use intention and online purchase intention is formulated based on the association of the Technological Acceptance Model (TAM) and chatbot characteristics. Data are collected from 412 online customers and structural equation modeling is applied to examine the hypotheses of the framework. Results reveal that TAM antecedents (i.e., perceived usefulness and attitude toward artificial intelligence) and chatbot characteristics (i.e., responsiveness, interactivity, and personalization) significantly influence intention to use chatbots. Additionally, use intention fosters online purchase intention. Attitude toward artificial intelligence plays a crucial role in increasing perceived usefulness of chatbots. Conclusion and implications are provided to induce customers’ usage behavior toward chatbots for online purchases.
Keywords: Chatbot; Online Purchase; Responsiveness; Artificial Intelligence